2021
DOI: 10.1145/3432948
|View full text |Cite
|
Sign up to set email alerts
|

Misinformation as a Window into Prejudice

Abstract: In the aftermath of the COVID-19 crisis, there has been a massive amount of misinformation both related to the condition, and a range of linked social and economic issues. We present a mixed methods study of misinformation debunked by Indian fact checking agencies since January 2020. Alongside this, we present an analysis of what politicians in India have been discussing in the overlapping period. We find that affective issues dominate misinformation, especially in the period following the lockdown in India. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 59 publications
1
14
0
1
Order By: Relevance
“…Regarding the first research question, the narrative threads of misinformation that have circulated in Saudi Arabia since the COVID-19 pandemic include the origin of COVID-19 and health advice coping with COVID-19. The findings suggest that misinformation could be tied in with sense-making, which is consistent with previous research [1,2]. It has been concluded that people turn to rumors as a way to cope with uncertainty.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the first research question, the narrative threads of misinformation that have circulated in Saudi Arabia since the COVID-19 pandemic include the origin of COVID-19 and health advice coping with COVID-19. The findings suggest that misinformation could be tied in with sense-making, which is consistent with previous research [1,2]. It has been concluded that people turn to rumors as a way to cope with uncertainty.…”
Section: Discussionsupporting
confidence: 89%
“…However, not all these languages have easy access to verified or reliable information, especially during this tough time. There are many studies investigating misinformation on Twitter related to COVID-19 in different languages (e.g., [1,9,[16][17][18]). For example, Jussila et al [17] explored misinformation related to COVID-19 in Finnish.…”
Section: Health Misinformation In the Arabic Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Journalistic objectivity often points to impartiality, nonalignment, non-involvement, and non-partisanship in building narratives but most consistently involves all of these characteristics. According to (Akbar, Panda, Kukreti, Meena, & Pal, 2021), journalism from the very broad perspective is the field of human endeavour that deals with the fabrication, processing, manufacturing and circulation of occurrences of events within local or national and to the global environment. The concept of journalism relates to employment, career and profession in addition to citizenship correspondences which involves assemblage and circulation of information, (Carlson & Lewis, 2015).…”
Section: The Concept Of Iot Drone Journalismmentioning
confidence: 99%
“…There is a strong need for developing technology to counter harmful online content in India. With the increasing popularity of social media platforms (e.g., Facebook, Twitter) [10] and instant messaging services (e.g., WhatsApp) in India, researchers have been studying the role of phenomena such as online misinformation [11] and hate speech [12] in Indian society and investigating ways to cope with their widespread prevalence.…”
Section: Motivationmentioning
confidence: 99%